Pengaruh Kombinasi Bambu terhadap Kualitas Oriented Strand Board (Effect of bamboo combination on the quality of Oriented Strand Board) - Adiaman RI Purba; Apri H Iswanto; Irawati Azhar (Jurnal Ilmu dan Teknologi Kayu Tropis, 2016)
Bamboo is a potential alternative material for wood based OSB. Evaluation of physical and mechanical properties of OSB from combined bamboo betung and bamboo tali was emphasized in the present research. Betung and tali bamboo were converted into strands with the length x width x thickness size of 7 cm x 2.5cm x 0.1cm, respectively. Strand were oven dried up to 7% of moisture content. Upon drying, strands wereblended with 5% isocyanat resin. After mat forming, furnish was pressed by hot press machine at 160 oC temperature for 5 minute and 30 kgcm-2 pressure. The prepared OSB was conditioned for 7 days at room temperature. The results showed that bamboo combination increased the physical and mechanical  properties of board. T/TB/T was the best combination in this experiment. OSB properties improved when betung bamboo was applied on the surface. Overall, the properties of board satisfied the requirement of  JIS A 5908 (2003) standard.Key word: betung bamboo, tali bamboo, isocyanate, OSB